(untitled) (Proceedings of International Conference on Special Education, 2015)
This research is motivated by problems in children who have’nt been able to hit badminton’s shuttlecock, children have difficulty servicing and return of serve. This research aims to upgrading the ability to hit badminton’s shuttlecock through a simple simulation. Simple simulation is a learning method presented in badminton several steps that simulated in the suspend ball game. This type of research is the single subject research with multiple baseline design across variables that aims to prove whether a simple simulation can upgrading the ability to hit badminton’s shuttlecock for children with mild intellectual disabilities. Type the size of the target behavior is the percentage obtained to compare response of children with a total answer should be multiplied by one hundred percent. While the data were analyzed using visual analysis of the data graph that consists of the analysis in condition and between conditions. The results of the data analysis and the analysis of conditions among conditions seen that before given treatment using a simple simulation on the baseline condition, her ability at the time of service and upon return of services remains low, after a given treatment her capability of return of services increased. It is recommended to use a simple simulation of the teachers in the teaching of badminton (subjects sports) for children with mild intellectual disabilities, for researchers as reference information in a learning method for prospective teachers and to students at the University as a good method of learning information in the course of teaching and learning, microteaching and so forth.